A hoard of Roman coins from the middle of the third century from Izvore, near Kosovska Mitrovica - Stamenković Sonja Z.; Samardžić Gligor M. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2013)
This paper presents a hoard of Roman coins of copper and its alloys found by chance on a site not far from Izvore, in the vicinity of Kosovska Mitrovica. There are 28 coins of the colonial issue minted in the middle of the third century, of which 26 are issued in Viminacijum, while the presence of the province of Dacia was detected on two pieces, with the effigies of the emperor Decius and his wife Etruscilla. The hoard includes money forged by the following rulers: Gordian III (1) , Philip I (9) , Philip II (1) Decius (3) Etruscilla (1) , Quint (4), Galus (6), Volusianus (1), and two illegible copies. It testifies about the importance of the colonial mint in the circulation of money in the mid-third century in the southern areas of the province of Upper Moesia and reveals a significant production of mint in Viminacijum.